ENGLISH-INDONESIAN GOOGLE TRANSLATE RESULT IN J.K. ROWLING'S HARRY POTTER AND THE ORDER OF THE PHOENIX: ANALYSIS OF NON-EQUIVALENCE PROBLEM - Alfian . (Jurnal Education and Development, 2022)
This study was aimed at analysing the non-equivalence problem encountered while translating the Harry Potter novel using Google Translate. Two software (AntConc and AntPconc) are used to cluster the most top ten-word class (Adjective, Noun, Verb, and Adverb) shown in the novel. AntConc was used to create a Wordlist to find the frequency of the words in the English text, while AntPConc was used to select the two text files (English and Indonesian version) to be checked as parallel texts.This present study concluded that Google translate has been able to translate and provide good suggestion translation to the top ten list of Noun, Adjective, Verb, and adverb. However, several non-equivalence in the word and above-word levels are still found. The equivalence problem appears in multiple lines of verbs, adjectives, and adverbs from those top lists. Several translation approaches must be utilized in the post-editing process to provide a more natural translation output.